2002
DOI: 10.1021/jp020731g
|View full text |Cite
|
Sign up to set email alerts
|

Transient Studies of Oxygen Removal Pathways and Catalytic Redox Cycles during NO Decomposition on Cu−ZSM5

Abstract: The identity of reactive intermediates and of active sites and the details of redox cycles and oxygen removal pathways during NO decomposition on well-characterized Cu-ZSM5 were examined by combining previous spectroscopic and steady-state kinetic studies with measurements of the rate of evolution of NO, N 2 O, NO 2 , N 2 , and O 2 during isothermal and nonisothermal kinetic transients. The oxygen coverages measured during reversible isothermal switches from He to NO/He mixtures showed that NO decomposition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Thus, the difference in contact between soot and the catalyst resulting from the different mixing of the solids is substantially attenuated since the NO/NO 2 couple acts as an oxygen carrier. Such a role of NO 2 as an oxygen carrier has also been reported in the case of deNO x reactions over metalozeolites [53].…”
Section: Catalytic Activitysupporting
confidence: 65%
“…Thus, the difference in contact between soot and the catalyst resulting from the different mixing of the solids is substantially attenuated since the NO/NO 2 couple acts as an oxygen carrier. Such a role of NO 2 as an oxygen carrier has also been reported in the case of deNO x reactions over metalozeolites [53].…”
Section: Catalytic Activitysupporting
confidence: 65%
“…Such sites would also be unable to participate in redox cycles requiring recombinative desorption steps. Our recent results 22,23 have shown, however, that oxygen removal steps involving NO 2 formation and decomposition of NO 2 and the use of NO as an oxygen carrier among distant redox sites allow all dimers to participate in NO decomposition redox cycles, irrespective of their relative proximity. …”
Section: Distributions Of Al-al Pairsmentioning
confidence: 90%
“…22,23 In this study, the NO decomposition rate data are correlated with the amounts of different Cu species in order to determine which Cu species are active for NO decomposition. Steadystate NO decomposition rates (N 2 + N 2 O formed per total Cu atom) are shown in Fig.…”
Section: Dependence Of Catalytic No Decomposition Rates On the Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent computational contributions of Goodman et al [38,42] stressed the eventual role of double-O-bridged copper pairs, i.e., [CuO 2 Cu] 2+ . Based on this knowledge, [CuO 2 Cu] 2+ has been included in some recent NO decomposition cycles [43][44][45] and is proposed to play a role in O 2 formation, either directly via the release of O 2 or indirectly via recombinative desorption requiring vicinal oxocations or NOmediated oxygen removal. However, in the latter studies, none of the double-O-bridged copper pairs that are proposed in the theoretical contribution of Goodman et al [38] were identified spectroscopically.…”
Section: Introductionmentioning
confidence: 99%